REVOLUSI TEKNOLOGI INFORMASI DAN PERUBAHAN SOSIAL DALAM PERSPEKTIF MATERIALISTIS, PENDEKATAN BARU TERHADAP PENDEKATAN IDEOLOGI SEBAGAI KENDARAAN PERUBAHAN SOSIAL - Rino Sundawa Putra (Fakultas Ilmu Sosial dan Ilmu Politik, 2011)
This paper attempts to analyze the phenomenon of social change as a result of the rapid development of technology, especially information technology, which gave birth to the so-called post-industrial information society (post industrial). As the foundation of his theory, the author will use the views and Marx's theory as a framework for analyzing social change. Social changes foreseen by Marx, where Marx's materialistic approach that emphasizes the development of technologies and industries that will give birth to new social system. Marx said the industrial revolution, since the invention of the steam engine, will give birth to capitalist society. Departing from Marx's view, the contemporary phenomenon of the background incidence of post-industrial information society (post industrial), is in response to the rapid development of technology, particularly information technology. If Marx said that industrial development will give birth to capitalist society, then this analysis using a revised view of the materialistic approach of Marx by Veblen, said that developments in sinformation technology as the climax of the development industry, will give birth to post-industrial information society.